“ENTREPRENEURSHIP & NEW VENTURE CREATION” KEY ELEMENTS OF THE ENTREPRENEURIAL ECOSYSTEM FACILITATING THE GROWTH OF ICT ENTREPRENEURS IN ITALY - Corno, Fabio; Lal, Richa; Colombo, Stefano (European Scientific Journal, ESJ, 2014)
This exploratory study examines the perceptions of Italian entrepreneurs about their experiences with their own new venture creations in Italy. The study utilizes the Ecosystem approach to examine the drivers of entrepreneurship. Integrating the theory from economics, sociology, and psychology, we argue that both the individual personality traits and the environment impact entrepreneurial activity. We used a mixed method approach with indepth interviews and surveys, followed by interviews with the Control Group. The findings suggest entrepreneurial spirit in Italy is high, and the socio-cultural environment is perceived as encouraging entrepreneurship. The business environment challenges confronting ICT entrepreneurs are related to government policies and programs, access to finance, perceived need for support towards knowledge and skill building and, finally, to exploring International markets. Theoretical and practical implications are discussed along with directions for future research.